CONSTRUCTION OF A THREE LEVEL SPLIT-LOT DESIGNS IN SUDOKU SQUARE DESIGN STRUCTURE (FUDMA JOURNAL OF SCIENCES, 2024)
In this research, a situation where blocking is required for a split lot design in order to tease out noise from the dependent variable (prevent factors other than that of interest influencing the outcome) was considered. Blocking for every stage of the design is administered, an elaborate construction procedure for the design was developed by infusing the ordinary split-lot design into a Sudoku Square design structure, the hybridisation gave it a convenient structure for the research. The linear model and the sum of squares of the design were derived, the ANOVA table was constructed and the table was used to analyse the whole system. The clear advantage of this design has been observed to be the additional source of variation, because the introduction of the Block Sum of Squares will reduce the Error Sum of Squares as a result makes it more efficient, but the fact that precision and cost are both functions of the number of sublots per step as well as the total number of items, comparison is complicated. The new design provides greater precision for main effects.
Keywords: Split-Plot; Split-lot; Sudoku Square design; Multistage process design; Blocking